Transforming Dogmatic Learning Into Critical Reasoning: How Problem-Based Learning Is Implemented in Islamic Religious Education - Durrotun Nafisah; Mundir; Imron Fauzi (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education is increasingly expected to develop students’ critical reasoning in response to contemporary social and moral challenges. However, classroom practices often remain doctrinal and text-centered, limiting students’ opportunities to engage religious concepts reflectively. This study aims to analyze how Problem-Based Learning (PBL) fosters students’ critical reasoning in Islamic Religious Education. Using a qualitative case study design, data were collected through classroom observation, interviews, and document analysis, and analyzed thematically to identify patterns in the implementation of PBL and its contribution to students’ reasoning processes. The findings show that PBL supports the transformation of doctrinal learning into a more reflective and analytical process through three main stages. First, problem identification encourages students to clarify issues and relate theological content to everyday realities. Second, problem diagnosis promotes causal reasoning and deeper examination of religious values. Third, solution synthesis helps students formulate reflective responses that connect cognitive analysis with ethical consideration and behavioral internalization. These findings indicate that PBL functions not only as an instructional strategy, but also as a pedagogical process that links theological understanding with critical reasoning and moral reflection. The study contributes to Islamic Religious Education by offering an integrative framework for designing more dialogic and reasoning-oriented learning.